Flexible thermoelectric fabrics based on self-assembled tellurium nanorods with a large power factor1. Issue 14 (14th April 2015) - Dun, Chaochao; Hewitt, Corey A.; Huang, Huihui; Montgomery, David S.; Xu, Junwei; Carroll, David L.
<x xml:space="preserve">Abstract</x> High performance thermoelectric fabrics with a room temperature power factor of 45.8 μW m−1 K−2 were fabricated based on self-assembled Te nanorods.